Contemporizing island biogeography theory with anthropogenic drivers of species richness. Issue 2 (19th December 2022) - Gleditsch, Jason M.; Behm, Jocelyn E.; Ellers, Jacintha; Jesse, Wendy A. M.; Helmus, Matthew R.
Abstract: Aim: Island biogeography theory states that species richness increases with habitat diversity and decreases with isolation from source pools. However, ecological theory must incorporate effects of human activity to explain contemporary patterns of biodiversity. We contemporized island biogeography theory by conceptualizing island trajectories of how species richness changes over time with accelerating land development and economic trade, which increase extinction and immigration rates, respectively. With this contemporized theory, we then articulate and empirically assess expected relationships of native, introduced and total species richness with natural and anthropogenic metrics of habitat diversity and isolation from source pools. Location: Greater Caribbean region. Time period: Database finalized in 2020. Methods: We built a database of 1, 042 native and introduced reptiles and amphibians (herps) for 840 Caribbean islands. For each island, we calculated natural and anthropogenic metrics of island habitat diversity and isolation from source pools and used linear model averaging to assess the expected relationships under the contemporized theory for 15 major herp clades. Results: Natural habitat diversity metrics exhibited positive relationships with native and introduced species richness, strengthening total species richness–area relationships across herp clades. Geographic isolation exhibited negative relationships with native and positive relationships with introduced species richness, weakening total species richness–isolation relationships. Economic area, based on developed land, and economic isolation, based on maritime trade, exhibited negative relationships with native species richness, but positive and negative relationships, respectively, with introduced species richness. Total species richness relationships with these two anthropogenic metrics were strongest in clades with many introduced species. Main conclusions: A contemporized island biogeography theory that includes the effects of land development and economic trade on species extinction and immigration explained current Caribbean herp species richness patterns. As human activity continues to accelerate, the contemporized theory we articulate here will increasingly predict island biogeography of the Anthropocene.